The World as Sacrament : The Eucharistic Cosmology of St Maximus Confessor - Heide, Daniel (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2026)
In The World as Sacrament, Daniel Heide offers a bold new interpretation of Maximus Confessor's ontology and cosmology. Approaching Maximus through the hermeneutic lens of Neoplatonism, the author argues for a doctrine of creation ex deo joined with the cosmic incarnation of the One Logos as the many logoi , or principles of creation. The result is a striking vision of sacramentality. The world is gift, the self-impartation of God in and through the Logos - a eucharistic cosmology which finds its completion in the anaphoric return of the cosmos back into God, mediated by the human as hierarch. This is the cosmic liturgy of St Maximus Confessor, the onto-dialectic of procession and return whereby God offers the gift of His own supra-essential Being for the life of the world - a gift freely offered back by the creature in gratitude (eucharistia) culminating in deification.